Effects of introducing a walk-in clinic on ambulatory care sensitive hospitalisations among asylum seekers in Germany: a single-centre pre–post intervention study using medical records - Celina Lichtl (BMJ Open)
Objective Measuring the effect of introducing a walk-in clinic on ambulatory care sensitive (ACS) hospitalisations among asylum seekers in a large state reception- and registration centre.Design and setting Pre–post intervention study using anonymous account data from a university hospital functioning as referral facility for a state reception- and registration centre in the third largest German federal state.Participants We included all asylum seekers residing in the reception centre and admitted to the referral hospital between 2015 to 2017.Interventions Establishment of an interdisciplinary walk-in clinic in the reception centre (02/2016).Main outcome measures International lists for ACS conditions for both adults and children were adapted and used to calculate the prevalence of ACS conditions among the population (primary outcome measure). The impact of the intervention on the outcome was analysed using a segmented Poisson regression to calculate incidence-rate ratios with respective 95% CIs, adjusted for age, sex and admission.Results The prevalence of ACS hospitalisations changed over time, as did the effect of age, sex and quarter of admission. Introducing the walk-in clinic reduced the prevalence of ACS hospitalisations among asylum seekers compared with the period before establishment of the clinic (incidence-rate ratios (IRR)=0.80 (0.65 to 1.00), p=0.054), but the effect was attenuated after adjustment for time trends. The average difference in prevalence of ACS hospitalisations compared with the period before establishment of the clinic, corrected for pre-existing time trends, age and sex of asylum seekers was IRR=1.03 ((0.69 to 1.55), p=0.876).Conclusions A walk-in clinic in reception centres may be effective to reduce ACS hospitalisations, but our study could not prove evidence for a measurable effect after full adjustment for time trends. Further research, ideally with parallel control groups, is required to establish evidence for the effectiveness of walk-in clinics in reception centres on reducing ACS hospitalisations.